PENGARUH HASIL BELAJAR MATA PELAJARAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA DI BIDANG JASA BOGA PADA SISWA SEKOLAH MENENGAH KEJURUAN - Cicilia Ristina (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
This study aims to determine the effect of learning outcomes of entrepreneurship education subjects on the interest in entrepreneurship in the field of catering services of students. This study included the type of ex-post facto research. The method of collecting data using the questionnaire and documentation method. The data analysis technique uses descriptive analysis and hypothesis testing using Product Moment correlation which is preceded by tests of analysis requirements for normality and linearity. The results showed that there was a positive and significant influence between the learning outcomes of entrepreneurship education subjects on the interest in entrepreneurship in catering services 46.7%, the entrepreneurship learning outcomes of most students in the good category, the interest in entrepreneurship was mostly in the low category.